Intra-observer reproducibility and inter-observer agreement of Fels skeletal age assessments among male tennis players 8-16 years - Sousa-e-Silva, Paulo (2023)
Skeletal age (SA) is an estimate of biological maturity status that is commonly used in sport-related medical examinations. This study considered intra-observer reproducibility and inter-observer agreement of SA assessments among male tennis players.